Infections with Gyrodactylus spp. (Monogenea) in Romanian fish farms: Gyrodactylus salaris Malmberg, 1957 extends its range. Issue 1 (December 2016) - Hansen, Haakon; Cojocaru, Călin-Decebal; Mo, Tor
Abstract Background The salmon parasiteGyrodactylus salaris Malmberg, 1957 has caused high mortalities in many Atlantic salmon, Salmo salar, populations, mainly in Norway. The parasite is also present in several countries across mainland Europe, principally on rainbow trout, Oncorhynchus mykiss, where infections do not seem to result in mortalities. There are still European countries where there are potential salmonid hosts forG. salaris but where the occurrence ofG. salaris is unknown, mainly due to lack of investigations and surveillance.Gyrodactylus salaris is frequently present on rainbow trout in low numbers and pose a risk of infection to local salmonid populations if these fish are subsequently translocated to new localities. Methods Farmed rainbow troutOncorhynchus mykiss (n = 340), brook trout, Salvelinus fontinalis (n = 186), and brown trout, Salmo trutta (n = 7), and wild brown trout (n = 10) from one river in Romania were sampled in 2008 and examined for the presence ofGyrodactylus spp. Alltogether 187 specimens ofGyrodactylus spp. were recovered from the fish. A subsample of 76 specimens representing the different fish species and localities were subjected to species identification and genetic characterization through sequencing of the ribosomal internal transcribed spacer 2 (ITS2) and mitochondrial cytochromec oxidase subunit 1 (cox 1). Results Two species ofGyrodactylus were found, G. salaris andG. truttae Gläser, 1974. This is the first timeG. salaris is diagnosed in Romania.Gyrodactylus salaris was found to infect rainbow trout, brown trout and brook trout in eight of the 12 farms examined. The prevalence and intensity of infections were generally low in all farms.Gyrodactylus truttae was present on brook trout in one farm and on wild brown trout in the river studied. This also represents the first record of this parasite in Romania. Analyses of sequences of thecox 1 gene ofG. salaris from Romania revealed four haplotypes, all previously undescribed. While it is not unlikely that the infections in Romanian fish farms originate directly from imported rainbow trout, the current data is not sufficient to conclude on this and does not exclude that the infections can originate from hosts in the local water systems. The study shows that there are still unknown populations and variants (haplotypes) ofG. salaris present in European rainbow trout aquaculture, all or many of them with unknown biological characteristics such as host specificity and virulence. As some strains might be pathogenic to Atlantic salmon, the importance of carrying out surveillance and keeping a high focus on control with import and export of live fish for aquaculture purposes is important. Conclusions Gyrodactylus salaris andG. truttae are for the first time found on salmonids in Romania. All mitochondrial haplotypes recovered were previously undescribed and this indicates that there is still an unknown diversity of this parasite present in localities not previously examined. The virulence of the haplotypes found in Romania is unknown and requires establishing.